Carbon fiber reinforced composite material, molded article, and method for manufacturing the same

JP2026165392APending Publication Date: 2026-10-14TORAY INDUSTRIES INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025057750
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2026-10-14

AI Technical Summary

Benefits of technology

【0009】 本発明によれば、炭素繊維強化複合材料が膨張することを利用し、本来の比剛性を維持しつつ廃棄製品からの優れた分別性が発現することに加え、接着剤の使用量を低減し異種材料と接合することが可能となり、優れた環境特性が発現する炭素繊維強化複合材料を提供することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165392000001
    Figure 2026165392000001
  • Figure 2026165392000002
    Figure 2026165392000002
Patent Text Reader

Abstract

By utilizing the expansion of carbon fiber reinforced composite materials, this invention provides a carbon fiber reinforced composite material that maintains its inherent specific stiffness while exhibiting excellent separability from waste products, reduces the amount of adhesive used, and enables bonding with dissimilar materials, thereby exhibiting superior environmental properties. [Solution] A carbon fiber reinforced composite material comprising a nonwoven fabric containing carbon fibers impregnated with a thermosetting resin, wherein the specific gravity of the molded product after heating at 250°C for 5 minutes is less than 1.0, and the thickness of the flat plate before and after heating satisfies the following relationship. 1.0 <ta / tb≦5.0 ta: Thickness of the molded product after heating at 250℃ for 5 minutes [mm] tb: Thickness of carbon fiber reinforced composite material before heating at 250°C for 5 minutes [mm]
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a molding material for carbon fiber reinforced composite materials that is suitably used for carbon fiber reinforced composite materials for general industrial members such as aerospace members, sporting goods, wind turbines, automobile outer panels, IC trays, and personal computer housings, and to a carbon fiber reinforced composite material molded using the same.

Background Art

[0002] Carbon fiber reinforced composite materials composed of carbon fibers and a matrix resin, utilizing their high specific strength and specific modulus, are used in structural materials for aircraft and automobiles, as well as in sporting applications such as tennis rackets, golf shafts, and fishing rods, and general industrial applications. When these carbon fiber reinforced composite materials themselves have a low specific gravity, further improved specific strength and specific rigidity can be achieved. On the other hand, as demand for these applications expands, the disposal of carbon fiber reinforced composite materials has become one of the issues in environmental problems. In addition, the production of carbon fibers has a large energy load, generating more than twice the amount of carbon dioxide compared to aluminum. Furthermore, when carbon fiber composite materials are used in combination with aluminum or plastics, an adhesive is basically required, and the generation of carbon dioxide during the production process of this adhesive also poses a problem.

[0003] To address the above issues, development of recycling technologies for carbon fiber reinforced composite materials has been actively carried out domestically and internationally to reduce environmental load, but there still remain problems in the technology for separating and collecting the carbon fiber composite materials in the preceding process. Generally, when used as structural materials, they are often mixed with metals, plastic materials, etc. to form a component with a single function. Therefore, it has been difficult to selectively separate and collect only the carbon fiber composite material from discarded structural materials.

[0004] Against this current situation, a molding material for carbon fiber reinforced composite materials containing a short carbon fiber web and an epoxy resin has been disclosed (Patent Document 1). In addition, a carbon fiber reinforced composite material containing discontinuous carbon fibers with a fiber length of 25 mm to 50 mm and an epoxy resin has been disclosed (Patent Document 2).

Prior Art Documents

[0005] [Patent Document 1] Japanese Patent Publication No. 2023-96359 [Patent Document 2] International Publication No. 2023 / 204131 [Overview of the project] [Problems that the invention aims to solve]

[0006] According to the molding material for carbon fiber reinforced composite materials described in Patent Document 1, there is no description regarding the parability of the resulting carbon fiber reinforced composite material, nor is there any description regarding joining with dissimilar materials. According to the carbon fiber reinforced composite material described in Patent Document 2, a carbon fiber reinforced composite material containing voids is proposed, but there is no description regarding the parability of the resulting carbon fiber reinforced composite material. Furthermore, since the carbon fiber reinforced composite material contains voids during molding, and the shape of the resulting carbon fiber reinforced composite material itself is fixed and voids are not generated by subsequent processes, when joining with dissimilar materials, it is necessary to use an adhesive as with general carbon fiber reinforced composite materials, and thus the use of an adhesive for joining with dissimilar materials is still necessary.

[0007] Therefore, the present invention aims to improve upon the shortcomings of the conventional technology by utilizing the expansion of the carbon fiber reinforced composite material itself, thereby providing a carbon fiber that maintains its original specific stiffness while exhibiting excellent separability from waste products, reduces the amount of adhesive used, enables bonding with dissimilar materials, and exhibits excellent environmental properties. [Means for solving the problem]

[0008] To solve these problems, the molding material for carbon fiber reinforced composite materials of the present invention has the following configuration. [1] A carbon fiber reinforced composite material comprising a nonwoven fabric containing carbon fibers impregnated with a thermosetting resin, wherein the specific gravity of the molded product after heating at 250°C for 5 minutes is less than 1.0, and the thickness of the plate shape before and after heating satisfies the following relationship. 1.0 <ta / tb≦5.0 ta: Thickness of the molded product after heating at 250℃ for 5 minutes [mm] tb: Thickness of carbon fiber reinforced composite material before heating at 250°C for 5 minutes [mm] [2] The carbon fiber reinforced composite material according to [1], wherein the tensile strength of the carbon fibers is 4.7 GPa or more and 10.0 GPa or less. [3] A carbon fiber reinforced composite material according to [1] or [2], wherein the number average fiber length of the carbon fibers is 2 mm or more and 90 mm or less. [4] A carbon fiber reinforced composite material according to any of [1] to [3], wherein the carbon fibers are recycled carbon fibers. [5] A carbon fiber reinforced composite material according to any of [1] to [4], wherein the carbon fiber mass content is 10% or more and 70% or less. [6] The basis weight of the carbon fiber nonwoven fabric is 10 g / m 2 More than 2000g / m 2 A carbon fiber reinforced composite material as described in any of the following [1] to [5]. [7] A carbon fiber reinforced composite material according to any one of [1] to [6], wherein the decomposition temperature of the carbon fiber reinforced composite material is 200°C or higher. [8] A carbon fiber reinforced composite material according to any one of [1] to [7], wherein the thermosetting resin is an epoxy resin. [9] A method for manufacturing a molded product, comprising placing a carbon fiber reinforced composite material described in any of [1] to [8] on a U-shaped mold, then placing a different material on top of it, and heating at a temperature above the glass transition temperature so that the carbon fiber reinforced composite material expands and fixes the different material to obtain a molded product. A molded article manufactured by the method for manufacturing a molded article described in

[10] [9], which is used as an insulator for a stator core. [Effects of the Invention]

[0009] According to the present invention, by utilizing the expansion of carbon fiber reinforced composite materials, it is possible to provide a carbon fiber reinforced composite material that exhibits excellent separability from waste products while maintaining its original specific stiffness, as well as reducing the amount of adhesive used and enabling bonding with dissimilar materials, thereby exhibiting excellent environmental properties. [Modes for carrying out the invention]

[0010] The carbon fiber reinforced composite material of the present invention will be described in detail below.

[0011] The present invention relates to a carbon fiber reinforced composite material comprising a nonwoven fabric containing carbon fibers impregnated with a thermosetting resin, wherein the specific gravity of the molded product after heating at 250°C for 5 minutes is less than 1.0, and the thickness of the flat plate before and after heating satisfies the following relationship. 1.0 <ta / tb≦5.0 ta: Thickness of the molded product after heating at 250℃ for 5 minutes [mm] tb: Thickness of carbon fiber reinforced composite material before heating at 250°C for 5 minutes [mm]

[0012] In the present invention, a nonwoven fabric containing carbon fibers refers to a form in which discontinuous strands and / or monofilaments of carbon fibers are dispersed in a planar manner, and examples include chopped strand mats, continuous strand mats, papermaking mats, carding mats, airlaid mats, etc. In the present invention, it is preferable that the nonwoven fabric contains 10% to 100% by mass of carbon fibers. This range is preferable because it allows the rigidity of the carbon fibers to be sufficiently reflected in the nonwoven fabric properties. More preferably, it is 50% to 100% by mass. The fibers contained in the nonwoven fabric are not limited as long as they are in a fiber shape, but examples include glass fibers and organic fibers. Furthermore, the nonwoven fabric may have a laminated structure, for example, a configuration in which a nonwoven fabric made of glass fibers and a nonwoven fabric made of carbon fibers are laminated.

[0013] The method for producing the nonwoven fabric in the present invention is not particularly limited, and for example, it can be produced by dispersing carbon fibers through a dry method, wet method, spunbond method, melt-blown method, air-laid method, scattering method or the like, and arranging them in a planar manner. Among these, the dry method is preferable in that carbon fibers with a wide range of fiber lengths can be used as a raw material. In the dry method, the expansibility of the carbon fiber composite material can be ensured by binding the web using a needle punch.

[0014] In the present invention, the fiber weight per unit area of the nonwoven fabric containing carbon fibers (hereinafter referred to as basis weight) is 10 g / m 2 to 2000 g / m 2 is preferable from the viewpoint of packing properties during transportation. In addition, the variation in the basis weight of the nonwoven fabric tends to be stable, and the drapability of the molding material for carbon fiber reinforced composite materials is stabilized. Reducing the number of stacked layers during lamination is preferable from the viewpoint of workability, and is 100 g / m 2 or more is more preferable. Further, when impregnating the molding material for carbon fiber reinforced composite materials with a resin, a shorter impregnation distance is preferable, and is 1000 g / m 2 or less, and further 500 g / m 2 or less is preferable.

[0015] In the present invention, the number average fiber length of the discontinuous carbon fibers constituting the nonwoven fabric is preferably 2 mm or more and 90 mm or less, more preferably 11 mm or more and 70 mm or less, and still more preferably 15 mm or more and 70 mm or less, from the viewpoint of stabilizing the expansion coefficient of the carbon fiber reinforced composite material.

[0016] In the present invention, from the viewpoint of environmental properties, it is more preferable that the carbon fibers are recycled carbon fibers. Here, the recycled carbon fibers refer to carbon fibers recovered using recycling techniques such as thermal decomposition, chemical decomposition, electrolytic oxidation, and mechanical pulverization, using as raw materials carbon fiber reinforced composite materials discarded as offcuts in the manufacturing process, molding materials for carbon fiber reinforced composite materials discarded as offcuts in the manufacturing process, or used carbon fiber reinforced composite materials, or carbon fibers obtained as offcuts in the manufacturing process.

[0017] In the present invention, the types of carbon fibers and recycled carbon fibers are not particularly limited, and a mixture of carbon fibers and recycled carbon fibers may be used as a raw material for nonwoven fabrics. On the other hand, recycled carbon fibers obtained from raw materials with clear types as described above are more preferable from the viewpoint of traceability, and it is further preferable that 90% or more of the recycled carbon fibers are composed of a single type. Examples of the types of carbon fibers and recycled carbon fibers of the present invention include polyacrylonitrile (PAN)-based, pitch-based, and rayon-based carbon fibers. Among these, PAN-based carbon fibers are preferred from the balance of strength and elastic modulus of the carbon fiber reinforced composite material. Commercially available carbon fiber products include "TORAYCA (registered trademark)" T1100GC, "TORAYCA (registered trademark)" T1100SC, "TORAYCA (registered trademark)" T800GC, "TORAYCA (registered trademark)" T800SC, "TORAYCA (registered trademark)" T700GC, "TORAYCA (registered trademark)" T300, "TORAYCA (registered trademark)" T300B, and "TORAYCA (registered trademark)" T700SC (all manufactured by Toray Industries, Inc.), "Pyrofil (registered trademark)" TR50S-3L, "Pyrofil (registered trademark)" TR50S-6L, "Pyrofil (registered trademark)" TR50S-15L, "Pyrofil (registered trademark)" TRH50-60M, "Pyrofil (registered trademark)" TRH40-50L (all manufactured by Mitsubishi Chemical Corporation), and the like.

[0018] The recycling technology used to obtain the recycled carbon fibers in the present invention is not particularly limited, and thermal decomposition, chemical decomposition, electrolytic oxidation, mechanical pulverization and the like can be used. In view of current recycling technologies, the thermal decomposition method or the chemical decomposition method is more preferable from the viewpoint of environmental load. Among them, the chemical decomposition method is particularly preferable because it can suppress the deterioration of the mechanical properties of the recycled fibers during recycling.

[0019] The carbon fibers of the present invention preferably have a tensile strength of 4.7 GPa or more and 10.0 GPa or less, and more preferably 5.5 GPa or more and 10.0 GPa or less, in order for the carbon fiber reinforced composite material to exhibit high mechanical properties. A tensile strength of 4.7 GPa or more is preferable because it exhibits the high specific stiffness required for carbon fiber reinforced composite materials. A tensile strength of 10.0 GPa or less is preferable because it exhibits the high specific strength required for carbon fiber reinforced composite materials. The tensile strength of the recycled carbon fibers in this invention may decrease from the tensile strength of the virgin carbon fibers during the recycling process described above. Therefore, since the tensile strength of the virgin carbon fibers that serve as the source of the recycled carbon fibers may not be achieved, it is more preferable that the tensile strength of the recycled carbon fibers be between 3.0 GPa and 10.0 GPa, and even more preferable that it be between 4.7 GPa and 10.0 GPa, and even more preferable that it be between 5.5 GPa and 10.0 GPa. A tensile strength of 3.0 GPa or higher is preferable because it allows for the high specific stiffness required for carbon fiber reinforced composite materials. A tensile strength of 10.0 GPa or lower is preferable because it allows for the high specific strength required for carbon fiber reinforced composite materials.

[0020] Examples of thermosetting resins in the present invention include unsaturated polyester resins, vinyl ester resins, epoxy resins, phenolic resins, urea resins, melamine resins, polyimide resins, cyanate ester resins, bismaleimide resins, benzoxazine resins, or copolymers and modified versions thereof, and resins blended with at least two of these. Among these, epoxy resins are preferred because they are sufficiently present on the carbon fiber surface when the carbon fiber reinforced composite material expands, thereby maintaining the strength of the carbon fiber reinforced composite material.

[0021] Examples of epoxy resins include bisphenol A type epoxy resin, bisphenol F type epoxy resin, dicyclopentadiene type epoxy resin, or epoxy resins modified from these. Examples of polyfunctional epoxy resins containing three or more epoxy groups in one molecule include triglycidylaminophenol type epoxy resin, glycidylamine type epoxy resin such as tetraglycidylamine type epoxy resin, glycidyl ether type epoxy resin such as tetrakis(glycidyloxyphenyl)ethane and tris(glycidyloxymethane), and epoxy resins modified from these, as well as brominated epoxy resins obtained by brominating these epoxy resins, or aliphatic epoxy resins made from aliphatic alcohols. Furthermore, two or more of these epoxy resins may be used in combination. Among these, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin are particularly suitable. Using these epoxy resins provides the further effect of improving the mechanical strength of carbon fiber reinforced composite materials compared to using highly rigid epoxy resins such as epoxy resins having a naphthalene skeleton in the molecule. This is because, while highly rigid epoxy resins tend to develop increased crosslinking density and thus become prone to distortion when cured quickly, the epoxy resins mentioned above are less likely to cause such problems. Furthermore, it is preferable to use aromatic epoxy resins and aliphatic epoxy resins in combination. This combination makes it possible to improve the mechanical properties of carbon fiber reinforced composite materials.

[0022] Commercially available bisphenol A type epoxy resins include "jER(registered trademark)" 825, "jER(registered trademark)" 826, "jER(registered trademark)" 827, "jER(registered trademark)" 828, "jER(registered trademark)" 834 (all manufactured by Mitsubishi Chemical Corporation), "EPICLON(registered trademark)" 850 (manufactured by DIC Corporation), "Epotote(registered trademark)" YD-128 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), "DER(registered trademark)"-331, and "DER(registered trademark)"-332 (both manufactured by Dow Chemical Company).

[0023] Commercially available bisphenol F type epoxy resins include "jER(registered trademark)" 806, "jER(registered trademark)" 807 (both manufactured by Mitsubishi Chemical Corporation), "EPICLON(registered trademark)" 830 (manufactured by DIC Corporation), and "Epotote(registered trademark)" YDF-170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.). Furthermore, commercially available alkyl-substituted tetramethylbisphenol F type epoxy resins include "Epotote(registered trademark)" YSLV-80XY (manufactured by Nippon Steel Chemical & Material Co., Ltd.).

[0024] As for aliphatic alcohols, those with 4 to 10 carbon atoms and a hydroxyl group bonded to a straight-chain or branched hydrocarbon group, and with a valent or higher hydroxyl group, are more preferable.

[0025] Examples of aliphatic alcohols with a valency of 2 or higher include 1,4-butanediol, 3-methyl-1,5-pentanediol, diethylene glycol, neopentyl glycol, 1,6-hexanediol, 1,9-nonanediol, cyclohexanedimethanol, propylene glycol, glycerin, and trimethylolpropane.

[0026] Commercially available aliphatic epoxy resins include "Denacol®" EX-321, "Denacol®" EX-313, "Denacol®" EX-314, "Denacol®" EX-411, "Denacol®" EX-412, "Denacol®" EX-512, "Denacol®" EX-521, "Denacol®" EX-612, "Denacol®" EX-614, and "Denacol®" EX-614B (all manufactured by Nagase ChemteX Co., Ltd.), "Epiol®" G-100 (manufactured by NOF Corporation), SR-GLG, SR-DGE, SR-TMP, SR-SEP, and SR-4GL (all manufactured by Sakamoto Pharmaceutical Co., Ltd.).

[0027] Examples of curing agents for epoxy resins include dicyandiamide, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, and polymer captans. More preferably, dicyandiamide or its derivatives are used. Cyandiamide easily imparts high flexural strength and heat resistance to the cured resin. It also easily imparts excellent storage stability to the epoxy resin composition. Furthermore, a derivative of dicyandiamide refers to a compound obtained by combining dicyandiamide with various other compounds. Similar to dicyandiamide, it is excellent in that it easily imparts high flexural strength and heat resistance to the cured resin, and also exhibits excellent storage stability to the epoxy resin composition. Here, a derivative refers to a compound obtained by reacting dicyandiamide with various other compounds. Two or more of these compounds may be used in combination as component (C).

[0028] Commercially available dicyandiamide products include DICY7 (manufactured by Mitsubishi Chemical Corporation), “Dicyanex®” 1400F (manufactured by Evonik Corporation), and “DYHARD®” 100 (manufactured by Alzchem K.K.).

[0029] Examples of dicyandiamide derivatives include those obtained by combining dicyandiamide with various compounds such as epoxy resins, vinyl compounds, acrylic compounds, and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide.

[0030] The heat resistance of the carbon fiber reinforced composite material of the present invention can be evaluated by its glass transition temperature, which is preferably 90°C to 250°C, and more preferably 100°C to 200°C.

[0031] The decomposition temperature of the carbon fiber reinforced composite material of the present invention is preferably 200°C or higher. A temperature of 200°C or higher is preferable because it preserves the mechanical properties of the molded product after heating at 250°C for 5 minutes. This decomposition temperature is the temperature at which the differential value of the TGA curve obtained by heating the carbon fiber reinforced composite material at 10°C / min is maximized, as determined by thermogravimetric analysis (TGA).

[0032] The carbon fiber reinforced composite material of the present invention is preferably in the form of a sheet or a flat plate. From the viewpoint of transportability, a sheet shape is more preferable as it improves packability.

[0033] The carbon fiber mass content in the carbon fiber reinforced composite material of the present invention is preferably 10% by mass or more and 70% by mass or less, and more preferably 20% by mass or less and 60% by mass or less. If the carbon fiber mass content is 10% by mass or more, the mass of the resulting fiber-reinforced composite material will not be excessive, and the advantages of fiber-reinforced composite materials, such as excellent specific strength and specific modulus, can be fully realized. Furthermore, if the carbon fiber mass content is 70% by mass or less, the impregnation of the epoxy resin composition into the reinforcing fibers is excellent.

[0034] As a method for producing the carbon fiber reinforced composite material of the present invention, autoclave molding, RTM molding, or press molding using a molding material for carbon fiber reinforced composite materials are preferably used. Among these, press molding is preferable because it allows molding while applying high pressure to the molding material for carbon fiber reinforced composite materials, thereby obtaining a carbon fiber reinforced composite material with high mechanical properties.

[0035] The carbon fiber reinforced composite material of the present invention is obtained by curing a molding material for carbon fiber reinforced composite materials. For example, by heating the carbon fiber reinforced composite material obtained by heating it at 150°C for 2 hours under a press pressure of 15 MPa in a press molding machine, and then demolding the material and heating it at 250°C for 5 minutes, a molded product with a specific gravity less than 1.0 can be obtained. Because the specific gravity is less than 1.0, it can be easily separated from metal and plastic materials with a specific gravity of 1.0 or higher using a water tank or specific gravity solution based on the difference in specific gravity. More preferably, the specific gravity is between 0.1 and 0.9. A specific gravity of 0.1 or higher is preferable because it allows the molded product to exhibit sufficient mechanical properties.

[0036] The carbon fiber reinforced composite material of the present invention satisfies the following relationship between its thickness before and after heating at 250°C for 5 minutes in a flat plate shape. 1.0 <ta / tb≦5.0 ta: Thickness of the molded product after heating at 250℃ for 5 minutes [mm] tb: Thickness of carbon fiber reinforced composite material before heating at 250°C for 5 minutes [mm]

[0037] When ta / tb is greater than 1.0, a carbon fiber reinforced composite material is placed on a U-shaped mold, then a different material is placed on top of it, and by heating at 250°C, the carbon fiber reinforced composite material expands, and it becomes possible to obtain a molded product in which the different material is fixed by utilizing this expansion pressure. This mechanical joining method is a different approach from conventional chemical joining methods that use adhesives, and is an innovative technology that can reduce the amount of adhesive used. Furthermore, when ta / tb is 5.0 or less, the resulting molded product can maintain sufficient mechanical properties. Preferably, ta / tb is between 1.1 and 4.8.

[0038] An example of a molded product manufactured using the above-described method for manufacturing molded products using a U-shaped mold is a stator core insulator. In this case, a stator core that constitutes a motor is used as the U-shape, and an insulator is manufactured using coil windings as a different material. This stator core insulator is an example of a product in which the carbon fiber reinforced composite material of the present invention is suitably utilized. [Examples]

[0039] The carbon fiber reinforced composite material of the present invention will be described in more detail below with reference to examples.

[0040] <Resin raw materials> The following raw materials were used to obtain the carbon fiber reinforced composite materials of each example. In the table, the numerical values ​​for each component in the resin composition column indicate the content, and unless otherwise specified, the unit is "parts by mass".

[0041] 1. Nonwoven fabric containing carbon fiber • r-T300: Recycled carbon fiber from "Torayca (registered trademark)" T300 (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 3.5 MPa) • r-T700: Recycled carbon fiber from "Torayca (registered trademark)" T700SC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 4.9 MPa) • r-T800: Recycled carbon fiber from "Torayca (registered trademark)" T800SC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 5.9 MPa) • r-T1100: Recycled carbon fiber from "Torayca (registered trademark)" T1100GC (manufactured by Toray Industries, Inc.) (Tensile strength of virgin carbon fiber: 7.0 MPa) • v-T700: "Torayca (registered trademark)" T700SC carbon fiber (Tensile strength 4.9 MPa) manufactured by Toray Industries, Inc.

[0042] 2. Epoxy resin • “Epotote (registered trademark)” YDF170 (manufactured by Nippon Steel Chemical & Material Co., Ltd.): Bisphenol F type epoxy resin • "Denacol®" EX-212 (manufactured by Nagase ChemteX Corporation): 1,6-Hexanediol diglycidyl ether

[0043] 3. Hardener • “jER Cure (registered trademark)” DICY7 (manufactured by Mitsubishi Chemical Corporation): Dicyandiamide

[0044] others • DCMU (manufactured by Tokyo Chemical Industry Co., Ltd.): 3-(3,4-Dichlorophenyl)-1,1-dimethylurea

[0045] (Preparation of epoxy resin composition) The resin compositions were prepared by mixing each component in the proportions listed in Tables 1 and 2.

[0046] (Production of recycled carbon fiber) • Recycled carbon fiber 1 (RC1) Process scraps from carbon fiber manufacturing were cut to the number-average fiber lengths listed in Tables 1 and 2 to produce recycled carbon fiber 1 (hereinafter referred to as RC1). The carbon fiber used was the type of carbon fiber listed in Tables 1 and 2.

[0047] • Recycled carbon fiber 2 (RC2) A carbon fiber reinforced composite material (600g) containing the types of carbon fibers listed in Tables 1 and 2 was cut to the number-average fiber length of the carbon fibers listed in Tables 1 and 2. Potassium hydroxide (100g) and N-methyl-2-pyrrolidone (5700g) were added to a 10000mL glass container, and the mixture was heated in an oil bath to 200°C for 2 hours. The resulting contents were filtered at 200°C, and the solid portion containing carbon fibers was washed with NMP and deionized water, and then dried to obtain recycled carbon fiber 2 (hereinafter, RC2).

[0048] • Recycled carbon fiber 3 (RC3) A carbon fiber reinforced composite material (600g) containing the types of carbon fibers listed in Tables 1 and 2 was cut to the number-average fiber length corresponding to the carbon fiber length listed in Tables 1 and 2. Recycled carbon fiber 3 (hereinafter referred to as RC3) was obtained by heating it to 500°C in an electric furnace in the presence of atmospheric pressure air for 3 hours.

[0049] (Production of nonwoven fabric) ·Non-woven fabric 1 (F1) The recycled carbon fibers are formed into a web sheet using a card and a cross wrapper, and then processed using a single-barb needle at a needle density of 50 needles / cm². 2Needle punching was performed to produce nonwoven fabric 1 (hereinafter referred to as F1).

[0050] ·Non-woven fabric 2 (F2) A dispersion with a concentration of 0.1% by mass was prepared, consisting of water and a surfactant (Nacalai Tesque Co., Ltd., polyoxyethylene lauryl ether (trade name)). Carbon fiber nonwoven fabric was manufactured using this dispersion and the recycled carbon fibers. The manufacturing apparatus consists of a cylindrical container with a diameter of 1000 mm, which serves as a dispersion tank and has an opening cock at the bottom, and a linear transport section (inclination angle of 30°) connecting the dispersion tank and the papermaking tank. An agitator is attached to the opening on the top surface of the dispersion tank, allowing recycled carbon fibers and the dispersion to be introduced through the opening. The papermaking tank is equipped with a mesh conveyor with a papermaking surface of 500 mm in width at the bottom, and a conveyor capable of transporting carbon fiber nonwoven fabric is connected to the mesh conveyor. Papermaking was performed with a carbon fiber concentration of 0.05% by mass in the dispersion, and the papermaking conditions were adjusted so that the carbon fibers were dispersed in monofilament form and isotropically dispersed in the in-plane direction. The manufactured nonwoven fabric 2 (hereinafter, F2) was dried in a drying oven at 200°C for 30 minutes.

[0051] (Fabrication of molding materials for carbon fiber reinforced composite materials) Two resin films were prepared by applying the epoxy resin composition prepared in the above (Preparation of epoxy resin composition) onto a film. The nonwoven fabric prepared in the above (Preparation of nonwoven fabric) was sandwiched between the two prepared resin films and impregnated with a roller to obtain a sheet-like molding material for carbon fiber reinforced composite material. At this time, the amount of epoxy resin composition was adjusted so that the volume content of carbon fibers in the obtained molding material for carbon fiber reinforced composite material was the value shown in Tables 1 and 2.

[0052] (Fabrication of carbon fiber reinforced composite materials) Using the molding material for carbon fiber reinforced composite materials obtained in the above (Preparation of molding material for carbon fiber reinforced composite materials), it was cured in a press machine under a pressure of 15 MPa at 140°C for 60 minutes to obtain a flat plate-shaped carbon fiber reinforced composite material measuring 300 × 400 mm × 2.0 mm.

[0053] (Manufacturing of molded products) By placing the carbon fiber reinforced composite material obtained in the above (fabrication of carbon fiber reinforced composite material) in an oven set to 250°C for 5 minutes, a molded product in the shape of a flat plate measuring 300 × 400 mm × 2.0 mm was obtained.

[0054] <Rating> The evaluation for each embodiment was carried out as follows. (Measurement of single-fiber strength of recycled carbon fiber) Using the recycled carbon fibers obtained through the above process (production of recycled carbon fibers), single-fiber strength and elongation measurements were performed in accordance with JIS R7606 (2000) under the following conditions. Furthermore, the strength (tensile strength) was calculated by dividing the maximum load on the SS curve by the single-fiber cross-section calculated from the density and basis weight. The sample size (n) was set to 5 or more. System: Tensilon Universal Tester RTI-1225 (A&D Company, Limited) • Load cell: 10N • Test speed: 1 mm / min • Sampling: 50 msec • Grip spacing: 25mm

[0055] (Measurement of the number-average fiber length of carbon fibers in nonwoven fabric) From the nonwoven fabric obtained by the above (preparation of nonwoven fabric), 400 carbon fibers were randomly extracted, and their fiber lengths were measured using an optical microscope. The number-average fiber length (Ln) calculated using the following formula was defined as the number-average fiber length of the carbon fibers. Number-average fiber length (Ln) = (ΣLi) / Nf Li: Measured fiber length (i = 1, 2, 3, ..., n) Nf: Total number of fibers measured in terms of length

[0056] (Measurement of specific gravity of molded products) The molded product obtained in the above (production of molded product) was cut into 150 mm x 1000 mm pieces, the cut surfaces were covered with tape, and the specific gravity was measured by the water displacement method. The measurement of specific gravity by the water displacement method was performed in accordance with JIS K7052.

[0057] (Evaluation of the parity of molded products) The six surfaces of the molded product obtained in the above (production of molded product) were submerged in a tank of water at 25°C. Cases where the product floated within 30 seconds were designated as A, cases where it floated for more than 30 seconds but less than 1 minute were designated as B, and cases where it floated for more than 1 minute were designated as C.

[0058] (Evaluation of the bonding properties of molded products) A laminate was fabricated by sandwiching a 30mm x 30mm x 1mm copper plate between two 30mm x 30mm x 1mm carbon fiber reinforced composite materials obtained in the above (fabrication of carbon fiber reinforced composite material) procedure. The laminate was placed in a U-shaped mold with a 30mm x 30mm x 3.5mm space and heated at 250°C for 5 minutes to obtain a molded body. When the molded body was pressed by hand, the case in which the laminate detached from the U-shape was designated as C, the case in which only the copper plate detached was designated as B, and the case in which it did not detach was designated as A.

[0059] (Examples 1-18) Using the types and mass parts of each component listed in Tables 1 and 2, epoxy resin compositions and recycled carbon fibers were prepared as described in (Preparation of epoxy resin composition) and (Preparation of recycled carbon fibers) above. The obtained recycled carbon fibers were measured as described in (Measurement of single-fiber strength of recycled carbon fibers) above, and the results are shown in Tables 1 and 2. Nonwoven fabrics were prepared using the manufacturing methods and basis weights described in Tables 1 and 2, as described in (Preparation of Nonwoven Fabrics) above. The obtained nonwoven fabrics were measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabrics), and the results are shown in Tables 1 and 2. Using the carbon fiber volume content listed in Tables 1 and 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). As described above (Preparation of carbon fiber reinforced composite material) and (Preparation of molded product), carbon fiber reinforced composite material and molded product were prepared. The obtained molded product was subjected to the specific gravities shown in Tables 1 and 2, as described above (Measurement of specific gravity of molded product), (Evaluation of preparative properties of molded product), and (Evaluation of bonding properties of molded product). At this time, good preparative properties and bonding properties were observed. (Example 19) An epoxy resin composition was prepared as described above (Preparation of epoxy resin composition) using the types and mass parts of each component listed in Table 2. For the virgin carbon fibers listed in Table 2, the recycled carbon fibers in the above (Measurement of single filament strength of recycled carbon fibers) were replaced with virgin carbon fibers, and the measurements were performed as shown in Table 2. Using the manufacturing method and basis weight described in Table 2, the recycled carbon fibers in the above (Nonwoven Fabric Manufacturing) were replaced with virgin carbon fibers to produce a nonwoven fabric. The obtained nonwoven fabric was measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabric), and the results are shown in Table 2. Using the carbon fiber volume content listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). As described above (Preparation of carbon fiber reinforced composite material) and (Preparation of molded product), carbon fiber reinforced composite material and molded product were prepared. The obtained molded product was subjected to the specific gravity shown in Table 2, as described above (Measurement of specific gravity of molded product), (Evaluation of preparative properties of molded product), and (Evaluation of bonding properties of molded product). At this time, good preparative properties and bonding properties were observed.

[0060] (Comparative Example 1) An epoxy resin composition was prepared using the types and mass parts of each component listed in Table 2, as described above (Preparation of epoxy resin composition). The virgin carbon fibers listed in Table 2 were measured as described above (Measurement of single filament strength of recycled carbon fibers), and the results are shown in Table 2. Using the manufacturing method and basis weight described in Table 2, a nonwoven fabric was produced by replacing the recycled carbon fibers in the above (Nonwoven Fabric Production) with virgin carbon fibers. The obtained nonwoven fabric was measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabric), and the results are shown in Table 2. Using the carbon fiber volume content listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). As described above (Preparation of carbon fiber reinforced composite material) and (Preparation of molded product), carbon fiber reinforced composite material and molded product were prepared. The specific gravities of the obtained molded product were obtained as shown in Table 2, as described above (Measurement of specific gravity of molded product), (Evaluation of preparative properties of molded product), and (Evaluation of bonding properties of molded product). At this time, the preparative properties and bonding properties were poor.

[0061] (Comparative Example 2) An epoxy resin composition was prepared using the types and mass parts of each component listed in Table 2, as described above (Preparation of epoxy resin composition). The virgin carbon fibers listed in Table 2 were measured as described above (Measurement of single filament strength of recycled carbon fibers), and the results are shown in Table 2. Using the manufacturing method and basis weight described in Table 2, the recycled carbon fibers in the above (Nonwoven Fabric Manufacturing) were replaced with virgin carbon fibers to produce a nonwoven fabric. The obtained nonwoven fabric was measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabric), and the results are shown in Table 2. Using the carbon fiber volume content listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). As described above (Preparation of carbon fiber reinforced composite material) and (Preparation of molded product), carbon fiber reinforced composite material and molded product were prepared. The specific gravities of the obtained molded product were obtained as shown in Table 2, as described above (Measurement of specific gravity of molded product), (Evaluation of preparative properties of molded product), and (Evaluation of bonding properties of molded product). At this time, preparative properties were good, but bonding properties were poor.

[0062] (Comparative Example 3) Recycled carbon fibers were prepared using the types and mass parts of each component listed in Table 2, as described above (Preparation of Recycled Carbon Fibers). The obtained recycled carbon fibers were measured as described above (Measurement of Single Yarn Strength of Recycled Carbon Fibers), and the results are shown in Table 2. Nonwoven fabrics were prepared using the manufacturing method and basis weight described in Table 2, as described in (Preparation of Nonwoven Fabrics) above. The obtained nonwoven fabrics were measured as described in (Measurement of Number-Average Fiber Length of Carbon Fibers in Nonwoven Fabrics), and the results are shown in Table 2. Using the carbon fiber volume content listed in Table 2, molding materials for carbon fiber reinforced composite materials were prepared as described above (Preparation of molding materials for carbon fiber reinforced composite materials). As described above (Preparation of carbon fiber reinforced composite material) and (Preparation of molded product), carbon fiber reinforced composite material and molded product were prepared. The specific gravities of the obtained molded product were obtained as shown in Table 2, as described above (Measurement of specific gravity of molded product), (Evaluation of preparative properties of molded product), and (Evaluation of bonding properties of molded product). At this time, the preparative properties and bonding properties were poor.

[0063] [Table 1]

[0064] [Table 2]

Claims

1. A carbon fiber reinforced composite material comprising a nonwoven fabric containing carbon fibers impregnated with a thermosetting resin, wherein the specific gravity of the molded product after heating at 250°C for 5 minutes is less than 1.0, and the thickness of the flat plate before and after heating satisfies the following relationship. 1.0<ta / tb≦5.0 ta: Thickness of the molded product after heating at 250°C for 5 minutes [mm] tb: Thickness [mm] of carbon fiber reinforced composite material before heating at 250°C for 5 minutes.

2. The carbon fiber reinforced composite material according to claim 1, wherein the tensile strength of the carbon fibers is 4.7 GPa or more and 10.0 GPa or less.

3. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the number-average fiber length of the carbon fibers is 2 mm or more and 90 mm or less.

4. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the carbon fiber is recycled carbon fiber.

5. A carbon fiber reinforced composite material according to claim 1 or 2, wherein the carbon fiber mass content is 10% or more and 70% or less.

6. The basis weight of the nonwoven fabric containing carbon fiber is 10 g / m². 2 More than 2000g / m 2 The carbon fiber reinforced composite material according to claim 1 or 2, which is as follows:

7. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the decomposition temperature of the carbon fiber reinforced composite material is 200°C or higher.

8. The carbon fiber reinforced composite material according to claim 1 or 2, wherein the thermosetting resin is an epoxy resin.

9. A method for manufacturing a molded product, comprising placing a carbon fiber reinforced composite material according to claim 1 or 2 on a U-shaped mold, then placing a different material on top of it, and heating at a temperature above the glass transition temperature so that the carbon fiber reinforced composite material expands and fixes the different material to obtain a molded product.

10. A molded article manufactured by the method for manufacturing a molded article described in claim 9, which is used as an insulator for a stator core.

Citation Information

Patent Citations

  • Molding material for carbon fiber-reinforced composite material, and carbon fiber-reinforced composite material

    JP2023096359A

  • Fiber-reinforced resin molded body and method for producing same

    WO2023204131A1